Strategi Pemasaran Berbasis Data Analitik: Studi pada UMKM di Era Digitalisasi - Zulkarnaini, Zulkarnaini; Haholongan, Rutinaias (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
This study aims to analyze the effect of data analytics utilization on the marketing effectiveness of MSMEs in the digitalization era. The independent variable (X) is the utilization of data analytics with indicators of data collection, data processing, data interpretation, and application in marketing. The dependent variable (Y) is the marketing effectiveness of MSMEs with indicators of market segmentation, promotional strategies, sales increases, and customer loyalty. The research method uses a quantitative approach with survey techniques and simple linear regression analysis with the help of SPSS. The results show that the utilization of data analytics has a significant effect on the marketing effectiveness of MSMEs with a significance value of 0.000 < 0.05 and an R² of 0.62. This means that 62% of the variation in marketing effectiveness can be explained by the utilization of data analytics, while the rest is influenced by other factors. The research findings show that the application of data analytics can increase the effectiveness of promotions and sales, although the ability to interpret data remains a major obstacle. In conclusion, a data analytics-based marketing strategy is an important step for MSMEs to strengthen competitiveness in the digital era, but it requires increased digital literacy and more optimal data management to achieve long-term results.